Diagnosis of Streptococcus pneumoniae pneumonia by quantitative enzyme linked immunosorbent assay of C-polysaccharide antigen. Issue 8 (August 1994) - Gillespie, S H; Smith, M D; Dickens, A; Raynes, J G; McAdam, K P
Abstract : AIMS--To evaluate the use of a quantitative enzyme linked immunosorbent assay (ELISA) detecting C-polysaccharide (PnC) antigen in sputum for the diagnosis of Streptococcus pneumoniae infection. METHODS--Specimens of sputum from 60 patients with acute community and hospital acquired pneumonia and infective exacerbations of obstructive airways disease were examined by semiquantitative culture and antigen ELISA. RESULTS--Using a cutoff value of 1 microgram/ml PnC antigen for a positive result, the sensitivity of this assay was 90.3%, specificity 93.1%, predictive value of a positive result was 93.5%, and the predictive value of a negative result 89.6%. CONCLUSIONS--Quantitation of C-polysaccharide antigen in sputum by ELISA distinguishes between carriage of oral bacteria which express PnC-like antigen and infection with S pneumoniae and compares favourably with other diagnostic methods.